New observations of chemically peculiar stars with ESPaDOnS†. Issue Volume 9:Issue S302(2013) (7th August 2014) - Khalack, V.; Yameogo, B.; Thibeault, C.; LeBlanc, F.
Abstract: We present the first results of the estimation of gravity and effective temperature for some poorly studied chemically peculiar stars that were recently observed with the spectropolarimeter ESPaDOnS at CFHT. We have analyzed the spectra of HD71030, HD95608 and HD116235 to determine their radial velocity, v sin i and the average abundance of several chemical species. We have also analyzed our results to verify for possible vertical abundance stratification of iron and chromium in these stars.